Elevated CO2 has concurrent effects on leaf and grain metabolism but minimal effects on yield in wheat. (20th July 2020) - Tcherkez, Guillaume; Ben Mariem, Sinda; Larraya, Luis; García-Mina, Jose M; Zamarreño, Angel M; Paradela, Alberto; Cui, Jing; Badeck, Franz-Werner; Meza, Diego; Rizza, Fulvia; Bunce, James; Han, Xue; et al.
Abstract: While the general effect of CO2 enrichment on photosynthesis, stomatal conductance, N content, and yield has been documented, there is still some uncertainty as to whether there are interactive effects between CO2 enrichment and other factors, such as temperature, geographical location, water availability, and cultivar. In addition, the metabolic coordination between leaves and grains, which is crucial for crop responsiveness to elevated CO2, has never been examined closely. Here, we address these two aspects by multi-level analyses of data from several free-air CO2 enrichment experiments conducted in five different countries. There was little effect of elevated CO2 on yield (except in the USA), likely due to photosynthetic capacity acclimation, as reflected by protein profiles. In addition, there was a significant decrease in leaf amino acids (threonine) and macroelements (e.g. K) at elevated CO2, while other elements, such as Mg or S, increased. Despite the non-significant effect of CO2 enrichment on yield, grains appeared to be significantly depleted in N (as expected), but also in threonine, the S-containing amino acid methionine, and Mg. Overall, our results suggest a strong detrimental effect of CO2 enrichment on nutrient availability and remobilization from leaves to grains. Abstract : A study of wheat grown at five FACE facilities around the world shows a low effect of CO2 on grain yield, and reveals relevant modifications in N and Mg metabolism.